Towards a Balanced Assessment of the Viability of Nuclear Energy in the Philippines - Yap, Josef Teofisto T (Archīum Ateneo, 2022)
Nuclear energy in the Philippines has been thrust into the spotlight by the administration of President Duterte. A committee created by Executive Order 116 was tasked to formulate a national position on a possible nuclear program. For nuclear energy to be a sustainable alternative, it must be accepted by society at large. Conventional wisdom surrounding the Bataan Nuclear Power Plant (BNPP) has branded this project as a white elephant leading to rejection of nuclear energy among a significant number of Filipinos, particularly members of civil society. This study presents evidence that the BNPP was operational at the time the administration of President Corazon Aquino decided to shut it down. Moreover, the risks related to the BNPP’s location are largely inconsequential. The BNPP became a white elephant because of an ill-advised political decision. Evaluating the viability of nuclear energy in the Philippines should therefore be balanced and deal solely with underlying technical and scientific issues, which are well known. Meanwhile, the role of nuclear energy in promoting a low-carbon society must be re-evaluated because of the sharp decline in the cost of variable renewable energy (VRE). If nuclear energy will eventually be incorporated in the plans of the Department of Energy (DOE), building a new large reactor would be too expensive. Two options are more feasible: revive the BNPP and/or invest in small module reactors (SMRs). Even if the latter has not yet been mainstreamed in the global energy market, SMRs are already on the radar of the DOE.